Management of Hypertensive Crises in Children: A Review of the Recent Literature - Bertazza Partigiani, Nicola; Spagnol, Rachele; Di Michele, Laura; Santini, Micaela; Grotto, Benedetta; Sartori, Alex; Zamperetti, Elita; Nosadini, Margherita; Meneghesso, Davide (Frontiers in Pediatrics, 2022)
Hypertensive emergency is a life-threatening condition associated with severe hypertension and organ damage, such as neurological, renal or cardiac dysfunction. The most recent guidelines on pediatric hypertension, the 2016 European guidelines and the 2017 American guidelines, provide recommendations on the management of hypertensive emergencies, however in pediatric age robust literature is lacking and the available evidence often derives from studies conducted in adults. We reviewed PubMed and Cochrane Library from January 2017 to July 2021, using the following search terms: “hypertension” AND “treatment” AND (“emergency” OR “urgency”) to identify the studies. 6 studies were analyzed, according to our including criteria. According to the articles reviewed in this work, beta-blockers seem to be safe and effective in hypertensive crises, more than sodium nitroprusside, although limited data are available. Indeed, calcium-channel blockers seem to be effective and safe, in particular the use of clevidipine during the neonatal age, although limited studies are available. On the other hand, it is important to avoid the use of ACE-inhibitors in newborns with postnatal age <30 days, due to the increased risk of hyperkalemia, elevated serum creatinine and death. However, further studies should be warranted to define a univocal approach to paediatric hypertensive emergencies.